Formulasi Sediaan Lipstik Dengan menggunakan Kombinasi Pewarna Alami Kulit Buah Jamblang (Syzigiumcuminii L) Dan VCO - Citra Pratiwi; Teti Indrawati; Ratna Djamil (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
The 96% ethanol extract of jamblang fruit peel has anthocyanin which has the potential to be used as a coloring agent for lipstick products. Jamblang fruit peel was extracted with 96% ethanol by kinetic maceration and tested for standard extract quality test, phytochemical screening, total anthocyanin values measured at 510nm and 700nm and antioxidant IC50 by DPPH method. The lipstick is made in 3 pH variations (Acid, Neutral and Alkali). Melting point, hardness, stability test with cycle test method, changes in shape, color and odor, smear test, pH test and skin irritation of male albino rabbits were also carried out in this study. Results showed that Jamblang fruit extract had antioxidant activity IC50 of 196.30 g/mL (average activity), total Anthocyanin value 0.2642%. Free from heavy metal content. The anthocyanin color in the extract of Syzigium cuminii L also changed according to the change in pH. The lipstick preparation is easy to apply, stable in three test cycles and does not irritate the skin of the shaved male albino rabbit. The conclusion, Jamblang fruit peel extract can be used as a natural dye in lipstick preparations.